2010
DOI: 10.1088/0022-3727/43/12/124006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic based modelling of radio-frequency driven atmospheric pressure plasmas

Abstract: Diagnostic based modelling (DBM) actively combines complementary advantages of numerical plasma simulations and relatively simple optical emission spectroscopy (OES). DBM is employed to determine absolute atomic oxygen ground state densities in a helium–oxygen radio-frequency driven atmospheric pressure plasma jet. A comparatively simple one-dimensional simulation yields detailed information on electron properties governing the population dynamics of excited states. Important characteristics of the electron dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
2
62
0
Order By: Relevance
“…Simulated spectra are fitted to the measurements to determine the gas temperature, by assuming that the rotational distribution is in thermal equilibrium with the neutral-gas temperature [42,43] as previously undertaken in high-pressure discharges for applications including, e.g. combustion [44], electric propulsion [45] and biomedicine [46][47][48]. Our spectrum simulation is based on molecular constants from [49] and line strength expressions from [50] for intermediate coupling of upper and lower state between Hund's case (a) and (b).…”
Section: Methodsmentioning
confidence: 99%
“…Simulated spectra are fitted to the measurements to determine the gas temperature, by assuming that the rotational distribution is in thermal equilibrium with the neutral-gas temperature [42,43] as previously undertaken in high-pressure discharges for applications including, e.g. combustion [44], electric propulsion [45] and biomedicine [46][47][48]. Our spectrum simulation is based on molecular constants from [49] and line strength expressions from [50] for intermediate coupling of upper and lower state between Hund's case (a) and (b).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] Thus far there is evidence that these plasmas may find applications in sterilisation, [1,2,[12][13][14][15] wound healing, [1,2,16] and cancer therapies. [3,[17][18][19][20][21][22][23] Low gas temperatures when operated in helium gas ($30-50 8C) [24,25] makes them highly suitable for such applications, as thermal damage to heat sensitive surfaces may be avoided. Of paramount importance to any future use of plasma devices in medicine are the end effects that such plasma sources induce in the liquid environment containing biological material.…”
Section: Introductionmentioning
confidence: 99%
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%